Binding of recombinant T cell receptor ligands (RTL) to antigen presenting cells prevents upregulation of CD11b and inhibits T cell activation and transfer of experimental autoimmune encephalomyelitis - Sinha, Sushmita (2010)
Recombinant T cell ligands (RTLs) ameliorate experimental autoimmune encephalomyelitis (EAE) in antigen specific manner. We evaluated effects of RTL401 (I-A(s) α1β1 + PLP-139-151) on splenocytes from mice with EAE to study RTL- T cell-tolerance-inducing mechanisms. RTLs bound to B, macrophages and DCs, through RTL-MHC-α1β1 moiety. RTL binding reduced CD11b expression on splenic macrophages/DC, and RTL401-conditioned macrophages/DC, not B cells, inhibited T cell activation. Reduced ability of RTL- incubated splenocytes to transfer EAE was likely mediated through macrophages/DC, since B cells were unnecessary for RTL treatment of EAE. These results demonstrate novel pathway of T cell regulation by RTL bound APCs.